Entrepreneurship and Waste Management: Cultivating Sustainable Solutions Through Education - Patnaik, Sweta; Isaacs, Shamil (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This paper examines the critical intersection of waste management and entrepreneurship within the context of sustainability-focused education, emphasizing the importance of integrating these themes into academic curricula to address pressing global environmental challenges. As the world grapples with issues such as resource depletion, excessive waste generation, and unsustainable business practices, the transformative role of education becomes increasingly evident. This study highlights how equipping students with the knowledge, skills, and entrepreneurial mindset to innovate for sustainability can serve as a powerful catalyst for change. The paper proposes a multidimensional pedagogical approach that combines theoretical understanding with practical application, fostering critical and innovative thinking. The paper also explores the role of experiential learning methodologies, such as problem-based learning, design thinking, and value co- creation, in fostering collaboration across disciplines and engaging stakeholders. By doing so, it seeks to prepare the next generation of environmentally conscious entrepreneurs capable of addressing waste management challenges while contributing to a more sustainable future.